(untitled) (Current Horticulture, 2024)
The experiment was conducted to find out the response of fertilizer application on yield and yield attributes of papaya (Carica papaya L.) var. Red Lady" during 2016-17 at Regional Horticultural Research Station, ASPEE College of Horticulture and Forestry, Navsari Agricultural University, Navsari (Gujarat). The experiment was laid out with nine treatments in a randomized block Design (RBD) and replicated thrice. The treatments included 100% RDF (200:200:250 g NPK/plant) as the control in four equal splits (2, 4, 6 and 8 MAP), 100 and 80% recommended dose of nitrogen and potash in 8 equal splits starting from 2nd month after planting at 30 days interval with or without foliar application of 1% Grade-IV micronutrient and novel organic liquid fertilizer at 2, 4, 6 and 8 month after planting. Results revealed that papaya var. Red Lady plants fed with 80% RDNK (160:200 g/ plant) and applied in 8 equal splits starting from 2 month after planting at 30 days interval with foliar application of novel organic liquid fertilizer at 2, 4, 6 and 8 month after planting gave maximum number of fruits per plant, average fruit weight (kg), diameter of fruit (cm), length of fruit (cm), yield (kg/plant and t/ha), maximum net realization and benefit : cost ratio.